Earnings, income and poverty among welfare leavers in Sweden - Anna Persson (Institute for Labour Market Policy Evaluation (IFAU), 2011)
Given the trend towards more active policies on reducing the take-up of welfare benefits, the consequences of leaving welfare on individual well-being constitutes a significant issue. This paper studies the disposable income and poverty among welfare leavers in Sweden during 19 years (1990-2008). Using a rich set of register data we are able to accurately measure disposable income and other financial and labor market outcomes and thereby give a well-founded analysis of the financial well-being of these individuals. We find that there are large and significant differences in post welfare financial situation among those that work full time after leaving welfare and those who work only a little or not at all. Labor work is associated with a higher probability of experiencing a financial gain after leaving welfare as well as a lower risk of repeated dependency. This relationship is not sensitive to changes in the business cycle, and is stronger for those that leave welfare after having received relatively high amounts of benefits. Groups that typically have a weaker attachment to the labor market are more sensitive to variations in the business cycle. Leavers who neither work nor receive benefits from social insurance are likely to be financially dependent on family members, and they are also more likely than other leavers to be in poverty. We conclude that leaving welfare is not always associated with becoming financially better off, and post welfare well being depend heavily on labor market outcomes.
Keywords: I31; J01; 330; welfare leavers; poverty; self-sufficiency; disconnected leavers; Sozialhilfeempfänger; Arbeitsmarkt; Einkommen; Armut; Schweden